Pembuatan Aplikasi Delivery Order pada Restoran Warung Mevvah - Ridwan Huangesa (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
In a business the most important thing is marketing, a good product without accompanied by a good marketing system will make the results of a business is not running maximal. Current conditions, marketing business through the virtual world is not a new thing. Business owners use the website as a means of promoting their products.Restaurant Warung mevvah is one of the emerging restaurants, and after being surveyed to local locations, Warung Mevvah Restaurant is about to expand its marketing using website based delivery system. The current condition of selling Restaurant Warung Mevvah not maximized. Based on the survey, consumers are more interested if the service Restaurant Warung mevvah not have to come to the location but via delivery. From this problem, in this final project will be designed a delivery order application at Warak Mevvah Restaurant based website.Buyers will be spoiled by shopping for food and drinks via the website and do not bother coming to the location. The input data will go into the sales database. The next process, employees will mendeliverykan orders in accordance with the address provided by consumers. With this service delivery service, sales will be expected to increase compared to before